An Analysis of Imperatives Used by the Teacher in EFL Classroom Interaction in Indonesian Secondary School - Rahmaeni Rahmaeni; Nurwafiqah Amirah Budi (Universitas Muhammadiyah Enrekang, 2024)
The way teachers communicate with students significantly affects the success of learning. Giving imperatives is one of the methods teachers use to communicate with students and enhance the effectiveness of the teaching and learning process. This research aimed to analyze the imperatives used by teachers in EFL classroom interactions in Indonesian secondary schools. The study employed a qualitative design. The subjects of the research were a representative English teacher and students from class XI IPS at SMAN 3 Enrekang, selected using a purposive sampling technique. Data were collected through classroom observations, video recordings, and interviews. The data were then analyzed using an interactive model of data analysis, which included data collection, data display, data condensation, and conclusion drawing/verification. The findings revealed that the teacher used different expressions when giving imperatives during the teaching and learning process, including positive, brief, and negative imperatives. The teacher employed imperatives to manage the classroom and instruct students. The use of imperatives was effective because students generally understood the teacher’s expectations, although the teacher sometimes needed to repeat certain imperatives to ensure student compliance. Students were able to grasp the imperatives easily because the teacher usually gave brief instructions. However, when the teacher used a different style of imperative, students sometimes became confused and struggled to respond immediately.